EVALUATION OF QUALITY DETERIORATION OF MARINE SHELLFISH DURING STORAGE AT DIFFERENT TEMPERATURES - Tri Winarni Agustini (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Study on evaluation of fish freshness has been carried out using several parameters such as chemical, sensory, and physical parameter in which each has its own merits and demerits. Oxidation-reduction potential and K value are a physico-chemical and chemical methods available in assessing fish freshness which are both considered as objective methods. This study aimed to find out the effect of different temperatures storage on ORP and K value change of marine shellfish. Material used in the study were black tiger shrimp (Penaeus monodon) and scallop (Amusium sp.). The experiment was laboratory experimental method. The samples were stored in room temperature (35±1oC) and refrigerated temperature (11±1oC). Analyses performed were ORP value (pH/ORP meter) and K-value (Ion-exchange chromatography method) and analysis were conducted in 4 replication. This study was carried out at laboratory of Fisheries Processing Technology, UNDIP Semarang and laboratory of PAU, UGM Yogyakarta. The ORP of black tiger shrimp and scallop stored at refrigerated temperature initially were 0.23 Volts and 0.32 Volts. There were a maximum ORP of 0.3 Volts (shrimp) and 0.35 Volts (scallop) in the 2nd day of storage. These ORP then decreased to – 0.12 Volts and 0.01 Volts for shrimp and scallop, respectively. At room temperature storage, the ORP ranging from 0.26 to 0.33 Volts. This value consecutively decreased to – 0.17 Volts (shrimp) and – 0.16 Volts (scallop) after 32 hours storage. Initial K value of black tiger shrimp and scallop stored at room temperature were 1.32% and 1.51%, respectively and after 32 hours storage there were an increase in K value to 6.14% and 5.43%. Increase in K value was slower for samples stored at refrigerated temperature than that of room temperature.